Pancasila Dalam Kajian Filsafat: Ontologi, Epistemologi Dan Aksiologi - Pristiwiyanto, Pristiwiyanto (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
Pancasila as the basis of the state of the Republic of Indonesia, its existence is very interesting to study from a philosophical aspect because before the existence of the Indonesian state, the Indonesian people in the pattern of life were still ethnic groups and the form of government was kingdoms that had their own territories and powers. Under these conditions, it is very difficult to find a philosophy for the formation of a country if it is not actually found a basic philosophy of the state that fulfills and provides protection for every tribe in the archipelago at that time. After independence, it turned out that a country with the spirit of unity was established, namely the unitary state of the Republic of Indonesia and the Pancasila as the basis of the state was established/ratified. This study from the philosophical aspect is interesting because it can determine the extent to which the philosophical aspects of Pancasila are formulated and fulfilled so that the existence of Pancasila is still relevant today. The characteristics of philosophy which are fundamental and deep, systematic, conceptual and holistic/wholesome are the basis when formulating the values ​​of Pancasila so that the truth value is very deep and universal. The approach used in this paper is a literature study with references to several books related to philosophy and Pancasila books. The results of the study in this writing fulfill the characteristic aspects of philosophy and its foundations, namely ontology, epistemology and axiology.